Bimbingan Teknis Projek Penguatan Profil Pelajar Pancasila (P5) Khusus Jenjang SD di Kecamatan Tinggimoncong Kabupaten Gowa - Hamzah, Rahma Ashari (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Technical guidance on the project to strengthen the profile of pancasila students is an activity carried out to provide participants with an understanding of how to implement the project to strengthen the profile of pancasila students in their respective educational units, which is a co-curricular activity in the independent curriculum. The aim of this activity is that all participants are able to understand the project to strengthen the profile of pancasila students, prepare the school ecosystem, design a project to strengthen the profile of pancasila students, document and report the results of the project to strengthen the profile of pancasila students, and be able to evaluate and follow up on the project to strengthen the profile of pancasila students. The method used is participatory for all participants, namely school principals and elementary school teachers, totaling 96 people from 24 schools and carried out on Wednesday-Thursday 18-19 December 2024 starting at 09.00 WITA-16.00 WITA at the District PKG Building Tinggimoncong, Jl. S. Dg. Jarung No. 320 Malino, Gowa Regency. The final result of this activity is participants' understanding regarding the implementation of the project to strengthen the Pancasila student profile, including in designing project modules and preparing project report cards. In this way, it can have a positive impact on schools, especially at the elementary school level, so that when implementing the project to strengthen the profile of pancasila students in each educational unit, the implementation is in accordance with the guidelines from the central ministry.